Regional Differences in Viral Growth and Central Nervous System Injury Correlate with Apoptosis - Richardson-Burns, Sarah M. (American Society for Microbiology, 2004)
Infection of neonatal mice with reovirus T3 Dearing (T3D), the prototypic neurotropic reovirus, causes fatal encephalitis associated with neuronal injury and virus-induced apoptosis throughout the brain. T3D variant K (VarK) is an antigenic variant that has a nearly 1 million-fold reduction in neurovirulence following intracerebral (i.c.) inoculation compared to T3D and a restricted pattern of central nervous system injury with damage limited to the hippocampus, sparing other brain regions. We wished to determine whether the restricted pattern of VarK-induced injury was due to a reduced capacity to replicate in or injure cortical, as opposed to hippocampal, tissue. We found that following i.c. inoculation, VarK grew to similar titers as T3D in the hippocampus but had significantly lower titers in the cortex. Both viruses grew to identical titers and infected the same percentage of cells in mouse primary hippocampal cultures (MHC). In mouse primary cortical cultures (MCC) both the number of infected cells and the viral yield per infected cell were significantly lower for VarK than T3D. VarK-induced apoptosis was limited to the hippocampus in vivo, and in vitro both viruses induced apoptosis equally in MHC but VarK induced significantly less apoptosis than T3D in MCC. Growth of T3D in MCC was reduced to levels comparable to those of VarK following treatment of MCC with caspase inhibitors. Conversely, induction of apoptosis in VarK-infected MCC with fatty acid synthase-activating antibody significantly enhanced viral yield. These results suggest that the decreased neurovirulence of VarK may be due to its failure to efficiently induce apoptosis in cortical neurons.